NEAT1 is overexpressed in Parkinson's disease substantia nigra and confers drug‐inducible neuroprotection from oxidative stress. Issue 10 (17th July 2019) - Simchovitz, Alon; Hanan, Mor; Niederhoffer, Naomi; Madrer, Nimrod; Yayon, Nadav; Bennett, Estelle R.; Greenberg, David S.; Kadener, Sebastian; Soreq, Hermona
ABSTRACT: Recent reports attribute numerous regulatory functions to the nuclear paraspeckle‐forming long non‐coding RNA, nuclear enriched assembly transcript 1 (NEAT1), but the implications of its involvement in Parkinson's disease (PD) remain controversial. To address this issue, we assessed NEAT1 expression levels and cell type patterns in the substantia nigra (SN) from 53 donors with and without PD, as well as in interference tissue culture tests followed by multiple in‐house and web‐available models of PD. PCR quantification identified elevated levels of NEAT1 expression in the PD SN compared with control brains, an elevation that was reproducible across a multitude of disease models. In situ RNA hybridization supported neuron‐specific formation of NEATl‐based para‐speckles at the SN and demonstrated coincreases of NEAT1 and paraspeckles in cultured cells under paraquat (PQ)‐induced oxidative stress. Furthermore, neuroprotective agents, including fenofibrate and simvastatin, induced NEAT1 up‐regulation, whereas RNA interference—mediated depletion of NEAT1 exacerbated death of PQ‐exposed cells in a leucine‐rich repeat kinase 2‐mediated manner. Our findings highlight a novel protective role for NEAT1 in PD and suggest a previously unknown mechanism for the neuroprotective traits of widely used preventive therapeutics.—Simchovitz, A., Hanan, M., Niederhoffer, N., Madrer, N., Yayon, N., Bennett, E. R., Greenberg, D. S., Kadener, S., Soreq, H. NEAT1 is overexpressed in Parkinson's disease substantia nigra and confers drug‐inducible neuroprotection from oxidative stress. FASEB J. 33, 11223–11234 (2019). www.fasebj.org